Intestinal Obstruction in a Child with Massive Ascariasis - Turyasiima, Munanura; Matovu, Paul; Kiconco, Gloria; Egesa, Walufu Ivan; Sunday, Phillip; Nakandi, Lydia; Musa, Kirya; Oluka, Denis; Byendera, Martin (Case Reports in Pediatrics, 2021)
Soil-transmitted helminths are so prevalent in the tropics and low developing countries. Pediatric clinical presentation of ascariasis, the most common helminth, as the intestinal obstruction is not only rare but also less described. We present a case of a 4- year-old girl with massive ascariasis. She presented with a 3-day history of acute abdominal pain associated with vomiting and an episode of passing long white roundworms, about 5 cm in length, through the nose. (e child had mild constipation and passed pellets of hard stool once in the last 72 hours. She was in fair general condition at the examination but had significant findings on abdominal examination. On palpation, there was a soft mass localized in the left paraumbilical area and no tenderness, with normal bowel sounds on auscultation. Exploratory laparotomy was sanctioned where roundworms (Ascaris lumbricoides), saucepan full, were delivered through a 2.5 cm enterotomy incision. Postoperative management was carried out, and the child discharged on the 7th day of treatment including a 3-day course of albendazole 400 mg daily.
Keywords: Intestinal Obstruction; Child; Ascariasis